2012
DOI: 10.1073/pnas.1112750109
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptome response to ionic liquid by a tropical rain forest soil bacterium,Enterobacter lignolyticus

Abstract: To process plant-based renewable biofuels, pretreatment of plant feedstock with ionic liquids has significant advantages over current methods for deconstruction of lignocellulosic feedstocks. However, ionic liquids are often toxic to the microorganisms used subsequently for biomass saccharification and fermentation. We previously isolated Enterobacter lignolyticus strain SCF1, a lignocellulolytic bacterium from tropical rain forest soil, and report here that it can grow in the presence of 0.5 M 1-ethyl-3-methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 77 publications
4
90
3
Order By: Relevance
“…The identification of this gene corroborates our previous observation that it is one of the most highly upregulated transcripts in E. lignolyticus when exposed to [C 2 mim]Cl 15 . Sequence analysis indicated that EilA is a homologue of proton antiporters, possessing 14 transmembrane helices that span the inner membrane.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The identification of this gene corroborates our previous observation that it is one of the most highly upregulated transcripts in E. lignolyticus when exposed to [C 2 mim]Cl 15 . Sequence analysis indicated that EilA is a homologue of proton antiporters, possessing 14 transmembrane helices that span the inner membrane.…”
Section: Resultssupporting
confidence: 78%
“…Enterobacter lignolyticus grows well in at least 380 mM (5.5%) 1-ethyl-3-methylimidazolium chloride (abbreviated as [C 2 mim]Cl) 14,15 , an IL that is a promising pretreatment solvent for biomass 6 . Using RNA-sequencing transcriptomics, we determined that E. lignolyticus responds to [C 2 mim]Cl exposure by the differential expression of 688 genes, resulting in a complex response with numerous phenotypic changes 15 . These include an increased production of cyclopropane fatty acids, scavenging of compatible solutes and regulation of membrane transporters.…”
mentioning
confidence: 99%
“…Microorganisms displaying IL tolerance have been screened using direct plating, growth in liquid culture and phenotypic microarrays (Deive et al 2011;Khudyakov et al 2012;Liu et al 2015;Nakashima et al 2011;Petkovic et al 2009;Petkovic et al 2010;Santos et al 2014;Simmons et al 2014;Singer et al 2011;Sitepu et al 2014).…”
Section: Discovering and Screening For Il Tolerant Microorganisms Relmentioning
confidence: 99%
“…In general, a colorimetric reagent, Redox Dye A (proprietary tetrazolium-based reagent from Biolog, Inc. Hayward, CA) is added to multi-well plates along with samples and incubated in the Omnilog instrument. Growth in each well is measured in Omnilog (OL) units, which calculate the change in tetrazolium redox dye color intensity attributed to dye reduction during cell respiration (Bochner and Savageau 1977;Khudyakov et al 2012). A few studies have utilized the OmniLog phenotypic microarray to screen for IL-tolerance Ruegg et al 2014).…”
Section: Discovering and Screening For Il Tolerant Microorganisms Relmentioning
confidence: 99%
“…DNA or reverse-transcribed RNA is then hybridized onto these spots and information on thousands of genes can be simultaneously collected. Various reports on genome-wide transcriptional profiling of soil microbes as well as numerous studies assessed changes in bacterial diversity after a disturbance or treatment through microarrays [142][143][144][145][146][147]. For example, the PhyloChip was used for microbial community profiling of disease suppressive soils [21].…”
Section: Dna Arraysmentioning
confidence: 99%